A blockchain ontology for DApps development - Besancon, L.; Ferreira da Silva, C.; Ghodous, P.; Gelas, J.- P. (IEEE Access, 2022)
Decentralized Applications, or DApps, provide distributed trusted applications that use blockchains. They are often composed of several services, such as transaction scalability protocols, decentralized storage and distributed computing solutions. In order to help formalize these applications, facilitate their development and improve their interoperability, we propose a novel blockchain Ontology focused on the concepts involving DApps. This ontology extends the existing EthOn ontology. It defines several key concepts related to DApps development, as well as the relations between these concepts. It features the formalization of known use cases and design patterns of blockchain technology through blockchain patterns. We use Semantic Web Rule language (SWRL) in order to define rules that express constraints on the formalized concepts. We then execute an inference engine and obtain new constraints on the properties of a defined DApp, such as its cost, based on the DApp characteristics and the services it uses. For illustration we show the inference of constraints between the Ethereum blockchain and its sidechain Polygon. We apply our research work in the field of blockchain video games. This application shows how to use the ontology to model DApps, and can be adapted to other fields.